One‐Dimensional Looped Chain and Two‐Dimensional Square Grid Coordination Polymers: Encapsulation of Bis(1, 2, 4‐Triazole)‐trans‐cyclohexane into the Voids. Issue 5 (29th January 2019) - Adarsh, Nayarassery N.; Dîrtu, Marinela M.; Guionneau, Philippe; Devlin, Eamonn; Sanakis, Yiannis; Howard, Judith A. K.; Chattopadhyay, Basab; Garcia, Yann
Abstract: Invited for the cover of this issue are Yann Garcia from Université catholique de Louvain, Belgium, and collaborators from partner universities and research centers. The cover image shows the square grid shape of an unprecedented Cu II coordination polymer with an "ancient temple architecture". Abstract : It opens new perspectives, for instance for drug storage or detection of toxic industrial chemicals … Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by Y. Garcia et al.